Conviction of the Innocent: Lessons From Psychological Research. 2012
DOI: 10.1037/13085-015
|View full text |Cite
|
Sign up to set email alerts
|

Life after wrongful conviction.

Abstract: Comparatively little research has examined the lives of exonerees postconviction. What research has been done in this area generally offers a clinical or criminological perspective on the tremendous consequences for the innocent (e.g., Campbell & Denov, 2004;Grounds, 2004;Westervelt & Cook, 2009). This chapter reviews the literature on the consequences of wrongful conviction, highlights current psychological research on the topic, offers suggestions for future research, and explores the impact research may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
8
22
0
Order By: Relevance
“…These findings are consistent with, and expand upon, previous research examining housing discrimination toward individuals with a criminal history (e.g., Evans & Porter, 2015;Furst & Evans, 2017) as well as audit studies (Kukucka et al, 2021;Zannella et al, 2020) demonstrating that rightfully and wrongfully convicted individuals experience similar levels of housing discrimination. These findings contribute to the growing literature outlining the difficulties that exonerees face post-release (e.g., Clow, 2017;Faison & Smalarz, 2020;Kukucka et al, 2021;Zannella et al, 2020). The results…”
Section: Discussionsupporting
confidence: 74%
“…These findings are consistent with, and expand upon, previous research examining housing discrimination toward individuals with a criminal history (e.g., Evans & Porter, 2015;Furst & Evans, 2017) as well as audit studies (Kukucka et al, 2021;Zannella et al, 2020) demonstrating that rightfully and wrongfully convicted individuals experience similar levels of housing discrimination. These findings contribute to the growing literature outlining the difficulties that exonerees face post-release (e.g., Clow, 2017;Faison & Smalarz, 2020;Kukucka et al, 2021;Zannella et al, 2020). The results…”
Section: Discussionsupporting
confidence: 74%
“…While much research has examined the antecedents of wrongful convictions—such as eyewitness misidentification (Wells et al, 2020), false confessions (Kassin et al, 2010), and forensic science errors (Kukucka, 2018)—comparatively little work has examined the consequences of wrongful conviction for exonerees. A smattering of qualitative studies has shed light on the many challenges that await exonerees upon their release, including mental and physical illness, poverty, unemployment, homelessness, and strained relationships, to name a few (e.g., Grooms, 2016; Grounds, 2004; Konvisser, 2015; Scott, 2010; Westervelt & Cook, 2010; see Clow et al, 2011 for a review ). For example, in the largest existing study of exonerees, Wildeman et al (2011) found that rates of clinical depression (44%) and PTSD (23%) were considerably higher than those in the general population.…”
mentioning
confidence: 99%
“…Very little research, however, has focused on the lives of individuals who have been wrongfully convicted post-incarceration (Westervelt & Cook, 2009). What research has been done has been predominantly qualitative (for a review, see Clow, Leach, & Ricciardelli, 2011) and has suggested that wrongfully convicted persons are essentially victimized by their wrongful conviction experiences and that their experiences can be likened to victims of torture (Weigand, 2009;Westervelt & Cook, 2009).…”
mentioning
confidence: 99%